Supplementary file to: Morrison, C. and Secker, J. (2015) Copyright Literacy in the UK: a survey of librarians and other cultural heritage sector professionals, Library and Information Research, 39(121), 75-97. (2015) - Morrison, C.; Secker, J.
No abstract available